Stigmergic coordination in FLOSS development teams: Integrating explicit and implicit mechanisms. (June 2016) - Bolici, Francesco; Howison, James; Crowston, Kevin
Abstract: The vast majority of literature on coordination in team-based projects has drawn on a conceptual separation between explicit (e.g. plans, feedback) and implicit coordination mechanisms (e.g. mental maps, shared knowledge). This analytic distinction presents some limitations in explaining how coordination is reached in organizations characterized by distributed teams, scarce face to face meetings and fuzzy and changing lines of authority, as in free/libre open source software (FLOSS) development. Analyzing empirical illustrations from two FLOSS projects, we highlight the existence of a peculiar model, stigmergic coordination, which includes aspects of both implicit and explicit mechanisms. The work product itself (implicit) and the characteristics under which it is shared (explicit) play an under-appreciated role in helping software developers manage dependencies as they arise. We develop this argument beyond the existing literature by working with an existing coordination framework, considering the role that the codebase itself might play at each step. We also discuss the features and the practices to support stigmergic coordination in distributed teams, as well as recommendations for future research.